Linking of 2-oxoglutarate and substrate binding sites enables potent and highly selective inhibition of JmjC histone demethylases. - Woon, E; Tumber, A; Kawamura, A; Hillringhaus, L; Ge, W; Rose, N; Ma, J; Chan, M; Walport, L; Che, K; Ng, S; Marsden, B; et al. (2012)
Select an isoform: Linking of cosubstrate and substrate binding sites enables highly selective inhibiton of isoforms of human histone lysine demethylases. The results should provide a basis for the development of potent and selective JmjC inhibitors, possibly suitable for clinical use. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.